The correlation between motivation and english language achievement among upper secondary school pupils - Abdul Kadir, Zahuren (2022)
Motivation is one of the important elements in learning a second language, as of this study, English. Various programmes and improvements are carried out on English subject in Malaysian schools aiming at producing pupils who are fluent in English after they graduate from schools as embedded in the Malaysia Blueprint Education 2013 – 2025. However, the mastery of English has not yet achieved the satisfactory level based on studies carried out globally and through public examinations. Therefore, this study aims to examine the correlation of motivation on English language achievement among pupils in Seremban, Negeri Sembilan (n=445). This study used Dörnyei’s (2005) L2MSS Theory and questionnaire developed by Dornyei’s (2005) too. The data obtained was analysed using SPSS version 26. Learning Experience (M=4.035, SD = 0.942) was the highest type of motivation among pupils in Seremban followed by Ideal L2 Self (M=3.853, SD = 0.899) and Ought-to L2 Self (M=3.6355, SD = 0.885). The data obtained was also analysed using the Mann-Whitney U. Statistically, there was no significant difference between gender and pupil’s achievement based on the three components in L2MSS (r < .05). Only Learning Experience (rˢ = -0.176, p = .001) exhibited correlation with pupil’s achievement, whereby Ideal L2 Self (rˢ = -0.296, p = .001) dan Ought-to L2 Self (rs = -0.068, p = .155) did not have any correlation. Thus, teachers need to motivate pupils in learning English. More studies could be done towards various types of Malaysian schools using instruments developed to suit the local pupils.